A directional dilemma in climate innovation - Kian Mintz-Woo (Journal of Responsible Innovation)
One branch of the responsible innovation literature involves the direction of innovation: if the public or decision-makers can or should direct innovation, how should innovation be directed? This paper explicates a case study where directionality – the plurality of plausible values for innovation – is directly implicated. In this case, a key technology may require a strategy for innovation, but there are contrasting normative reasons to drive that innovation in different ways, reflecting two distinct moral values, ‘effectiveness’ and responsiveness to ‘need’. In this case, carbon dioxide removal, these values may well conflict. Strategically deploying carbon dioxide removal in a cost-effective manner would tend to support siting it in regions where there are significant oil and gas operations. In contrast, strategically deploying carbon dioxide removal in response to need would tend to support siting it in regions where expected demand for the technology is required for development.